2014
DOI: 10.1186/1471-2407-14-832
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal carcinoma with paranasal sinus invasion: the prognostic significance and the evidence-based study basis of its T-staging category according to the AJCC staging system

Abstract: BackgroundTo evaluate the prognostic significance of paranasal sinus invasion for patients with NPC and to provide empirical proofs for the T-staging category of paranasal sinus invasion according to the AJCC staging system for nasopharyngeal carcinoma.MethodsThe clinical records and imaging studies of 770 consecutive patients with newly diagnosed, untreated, and nondisseminated NPC were reviewed retrospectively. The overall survival, distant metastasis-free survival, and local relapse-free survival of these p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 32 publications
1
30
3
Order By: Relevance
“…Tian et al. retrospectively analyzed 770 patients with stage I–IV disease (by the AJCC seventh edition staging system). They reported paranasal sinus invasion in 182 of 770 (23.6%) patients, with invasion of the sphenoid, maxillary, and ethmoid sinuses being seen in 162 of 770 (21.0%), 86 of 770 (11.2%), and 38 of 770 (4.9%) patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tian et al. retrospectively analyzed 770 patients with stage I–IV disease (by the AJCC seventh edition staging system). They reported paranasal sinus invasion in 182 of 770 (23.6%) patients, with invasion of the sphenoid, maxillary, and ethmoid sinuses being seen in 162 of 770 (21.0%), 86 of 770 (11.2%), and 38 of 770 (4.9%) patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sphenoid sinus involvement was most common (163/943, 17.3%); ethmoid, maxillary, and frontal sinus involvements were seen in 50 of 943 (5.3%), 27 of 943 (2.6%), and two of 943 (0.2%), respectively. Tian et al [16] retrospectively analyzed 770 patients with stage I-IV disease (by the AJCC seventh edition staging system). They reported paranasal sinus invasion in 182 of 770 (23.6%) patients, with invasion of the sphenoid, maxillary, and ethmoid sinuses being seen in 162 of 770 (21.0%), 86 of 770 (11.2%), and 38 of 770 (4.9%) patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…T staging, including involvement of the paranasal sinuses, can reflect the risk of local failure . Paranasal sinus involvement is common; previous studies showed an incidence of 16%‐39.4% . However, there is no consensus on the staging of paranasal sinus invasion in the current staging systems.…”
Section: Introductionmentioning
confidence: 99%
“…NPC with paranasal sinus invasion is considered T3 classification in the eighth edition of the AJCC staging system, whereas the Chinese 2008 staging system, which is widely used in southern China, defines it as T4 disease . There are limited studies about the prognostic value and staging classification of NPC with paranasal sinus invasion, especially in the IMRT era with the current AJCC staging system . Whether different types of paranasal sinus invasion should be classified as the same T classification is still controversial .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation